Um ghul dentro do peito: Do conto “O Infeliz”, de Abd Arrahman Munif - Aprigliano, Adriano (Revista Criação & Crítica, 2020)
In “The Wretched One”, Almankūd, by Jordanian writer ‘Abd Arraḥmān Munīf (1933-2004), the narrator harks back to his child memories about his bedouin uncle Underneath the Family tale, there emerges a scathing look on the conflict between modern urban and traditional nomad cultures in desert regions of the Middle East. I present here the first translation of this short story into Brazilian Portuguese. In the Notes to the translation, I comment on peculiarities of Literary Arabic and how I treated them in Portuguese. In the Introduction, I summarize the author’s Life and Works, as well as the structure and main themes in “The Wretched one”.